Engineered Nanomaterials Health and Safety - Marius Avramescu, Sorin; Akhtar, Kalsoom; Fierascu, Irina; Bahadar Khan, Sher; Ali, Fayaz; Asiri, Abdullah M. (IntechOpen, 2020)
Nanotechnologies are extremely diverse, bringing about new opportunities in human lives through countless applications. This book is intended to emphasize a new perspective of knowledge on the environmental and human health impact of engineered nanoparticles in general with a focus on Ag nanoparticles as the most studied and manufactured material in this field. The authors are renowned specialists from different countries and their expertise allows us to fulfill the difficult task of presenting some insightful data from this vast field. This book can be considered an important reference for chemists, biochemists, physicians, and materials scientists working with and developing nanoparticle systems with a focus on the possible impact on human health.In this book, readers will find a brief history of the nanoparticles, the need for their development, preparation methods, and useful applications. This book provides an overview of metal nanoparticles for a broad audience: beginners, graduate students, and specialists in both academic and industrial sectors.